Training and Integrating Local People into the Workforce - UNCTAD; World Bank (World Bank, Washington, DC, 2018)
This note provides guidance on how to assist people from surrounding areas in gaining formal employment at the investment. Formal employment is a major expected benefit of agricultural investments. Yet investors experience difficulties in employing people from surrounding areasdue to gaps in skills and education. The inclusion of local people in the formal workforce is a key element of partnerships between local communities and investors. This inclusion can be facilitated by dedicated training programs and strategies to improve integration.